Utilization of smartphones in making learning videos for teachers of ABA Kindergarten Sidoharjo - Muhammad Muttaqien; I Wayan Nain Febri (Universitas Muhammadiyah Magelang, 2022)
The government's policy of implementing the Work from home system as a form of handling the spread of the COVID-19 virus affects many aspects, including education. Education, which was previously carried out face-to-face, has been shifted to online learning. Online learning can be done using a number of formats, one of which is a video that contains elements of images and sound. Video creation can be produced simply, for example, using a smartphone, but not all teachers are able to optimize the tool. Therefore, empowerment team in collaboration with ABA kindergarten Sidoharjo, Sleman, Daerah Istimewa Yogyakarta was carried out with the aim of providing training to teachers in optimizing the use of smartphones as a means of producing learning video content. The activity begins with the pre-production stage, namely observation and discussion, the production stage, namely training in learning video production with smartphones, the post-production stage, namely editing training with the VN application on smartphones. Besides, empowerment team also provided grants green screen, audio equipment, and a set of studio lights for video production. The result of this program showed that teachers are able to improve the quality of learning videos just by using a smartphone.